Aristas de la écfrasis: perspectivas de asedio para una modalidad poética compleja - Jesús Ponce Cárdenas (Mélanges de la Casa de Velázquez, 2025)
The most widespread definitions of ekphrasis tend to emphasise the descriptive nature of a concept central to the study of inter-artistic relations: “verbal representation of a visual representation” (Heffernan), “literary description of a visual work of art” (Pineda). This essay analyses an anonymous Latin epigram and several compositions by seventeenth-century writers (Giovan Battista Marino, Gaspare Murtola, Gabriel de Roa, Ana Ponce de León, Manoel de Galhegos, Pietro Mellini...) referring to paintings (Caravaggio, Maíno, Velázquez) with the aim of highlighting any points of contrast that the praxis of transposing Baroque art poses in relation to the ekphrasis of our time. The pictorial genres examined include portraiture and history painting. The study also seeks to identify some of the limits or discrepancies posed by the sometimes overly mechanical application of the concept of ekphrasis to a wide range of modern poetic compositions in dialogue with paintings.